Pendampingan Rumah Contoh Pencegahan Stunting di Desa Ayula Kabupaten Pohuwato melalui Program RTP2S - Nurmiah; Febriyanti Karim; Indriani Umar; Moh Eran; Bulan Suci Ramadhani; Nevi Kurniawati; Titi Hawanda Methania Cono (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Pohuwato Regency has a high prevalence of stunting, namely 34.6% in 2021, which successfully decreased to 6.4% in 2022. However, continuous prevention efforts are still needed to achieve the zero-stunting target. One of the main challenges is the low level of knowledge among housewives in cultivating nutraceuticals in their home gardens, resulting in suboptimal food self-sufficiency for families. The Stunting Prevention Pioneer Household Program (RTP2S) was designed by the government with a family-based approach through a pilot house model in stunting-prone villages that also experience problems with sanitation, clean water, and food security. The objective of this community service activity is to support the implementation of the RTP2S program through mentoring model homes in Ayula Randangan Village as a step towards becoming a BESTI (Stunting-Free) Village. The community service was carried out through socialization, technical guidance, and hands-on training applied to one model home. The technology and innovation approach was carried out by applying the concept of combining architecture and agriculture through a model design of healthy houses and productive yards that grow nutritious (nutraceutical) plants to create a sustainable food house area. This program integrates healthy home education, sanitation improvements, and the use of yards for cultivating plants, fish, and livestock on a household scale. The results of the activity show that the implementation of the RTP2S pilot house can serve as a visual model and practical example that is easy for the community to follow. One pilot house was successfully built and equipped with a productive yard for vegetables, fish, and chickens. The community response was quite positive, and this pilot house has begun to be used as a reference by other residents in Randangan. These findings indicate that the pilot house approach in RTP2S is effective in promoting family nutritional independence and can be developed more broadly towards a Food Security Village and stunting-free area.